2019
DOI: 10.1002/solr.201800280
|View full text |Cite
|
Sign up to set email alerts
|

Sb2(Se1‐xSx)3 Thin‐Film Solar Cells Fabricated by Single‐Source Vapor Transport Deposition

Abstract: The properties of Sb2(Se1‐xSx)3 alloy films can be continuously tuned by changing its composition, enabling potentially better device efficiency compared to the Sb2S3 or Sb2Se3 counterparts. Fabrication of Sb2(Se1−xSx)3 films with good uniformity and orientation are prerequisites to realize their full potential. Here, pure‐phase and high‐uniformity Sb2(Se1‐xSx)3 absorbers are successfully produced via a vapor transport deposition method employing a single evaporation source. Increasing the travelling distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 33 publications
(20 reference statements)
0
17
1
Order By: Relevance
“…Besides, H 2 O 2 treated CdS layer can improve the CdS/Sb 2 (S,Se) 3 heterojunction quality, thereby, enhancing the device PCE from 5.42% for pure CdS to 6.07% in the modified case. [ 77 ]…”
Section: Band Alignment Optimizationmentioning
confidence: 99%
“…Besides, H 2 O 2 treated CdS layer can improve the CdS/Sb 2 (S,Se) 3 heterojunction quality, thereby, enhancing the device PCE from 5.42% for pure CdS to 6.07% in the modified case. [ 77 ]…”
Section: Band Alignment Optimizationmentioning
confidence: 99%
“…Studies revealed that Sb 1.9 S 2.2 Se 0.9 has a bandgap of 1.52 eV, falling into the ideal bandgap in the Shockley–Queisser limit. During the publication of the review, a certified PCE of 6.14% and a record efficiency of 6.3% for Sb 2 (S x Se 1−x ) 3 solar cells were realized by using hydrothermal method and VTD method to fabricate Sb 2 (S x Se 1−x ) 3 films, respectively …”
Section: Antimony Chalcogenide Solar Cellsmentioning
confidence: 99%
“…During the publication of the review, a certified PCE of 6.14% and a record efficiency of 6.3% for Sb 2 (S x Se 1Àx ) 3 solar cells were realized by using hydrothermal method and VTD method to fabricate Sb 2 (S x Se 1Àx ) 3 films, respectively. [115,116]…”
Section: Mesoporous Sb 2 (S X Se 1àx ) 3 Sensitized Solar Cellsmentioning
confidence: 99%
“…Through impurity incorporation, or an optimized deposition process, the absorber efficiency can be improved to 6.30% and 7.6%, respectively. [ 245–247 ] Another proposed strategy is to build an electric field to separate the electron–hole pairs. Considering the low p‐type conductivity in Sb 2 Se 3 , Chen et al.…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationsmentioning
confidence: 99%
“…Thus, by mapping a series of materials, including PbX (X = S, Se, Te), Sb 2 Te 3 , Bi 2 X 3 (X = Se, Te), and inorganic halide perovskites, into a 2D space with the ES and ET as two coordinates, they found MVB had well‐defined borders to covalent, and iono‐covalent regions, indicating its distinction. [ 229–307 ] Such a map demonstrated that the MVB mechanism approximately possessed one shared electron and moderate electron transfer between adjacent atoms. This predictive model can also give rise to the favorable characteristics in above materials, including large Born effective charge, high optical dielectric constants, strong optical interband transition, etc.…”
Section: Conclusion and Perspectivementioning
confidence: 99%